Proactive Therapeutic Drug Monitoring of TNF Antagonists in Inflammatory Bowel Disease. Issue 9 (3rd May 2018) - Roblin, Xavier; Riviere, Pauline; Flamant, Mathurin; Veyrard, Pauline; Poullenot, Fabien; Paul, S; Laharie, David
Abstract: Background: Proactive therapeutic drug monitoring (TDM) to titrate tumor necrosis factor (TNF) antagonists has emerged recently as a tool to routinely monitor drug concentration to achieve target levels in patients with quiescent inflammatory bowel disease (IBD). Methods: The purpose of the present review article was to present available data exploring the concept of proactive TDM. Results: While several observational studies have identified an association between proactive TDM and better IBD outcomes, 2 randomized controlled studies did not confirm this advantage. Conclusions: Based on the evidence to date, proactive TDM cannot be recommended in daily practice. However, analysis is hampered by the low level of evidence for the cutoffs used and the need for point-of-care assays. Regarding economic issues and de-escalating strategies, proactive TDM may have several future indications in IBD. Exploratory studies on proactive TDM with newly available biologic agents in IBD are also awaited.